Parental satisfaction and engagement with school quality indicators: a comparative study - Mansour, Khiati; Ahmed, Mahfooz; Al-Hidabi, Dawood Abdulmalek Yahya (International Institute for Muslim Unity (IIMU), International Islamic University Malaysia, 2024)
This study aims to evaluate parental satisfaction and engagement with school quality indicators, understand the impact of parental involvement on student outcomes, and provide practical implications for educational policymakers. It also seeks to contribute to existing literature, serve as a foundation for future research, and emphasize the importance of effective communication between schools and parents. parental satisfaction and engagement with school quality indicators. The relationship between parents and educational institutions is paramount for the overall development of students and the educational system’s effectiveness. Parents play a vital role in the educational process, and their understanding of school quality indicators and their level of satisfaction and engagement with these indicators can significantly influence educational outcomes. Drawing on the NAMA Theory of Change Indicators (TOC), this study employs a quantitative approach to report part of the findings of the recent school evaluation visits to the 63 NAMA Foundation-supported schools across Tanzania, Indonesia, and Kyrgyzstan by a team of 23 trained assessors. The evaluation was conducted before and after the NAMA intervention to access the parent’s feedback on their child’s school life, learning success, and school values and culture. The findings reveal a significant improvement across all NAMA TOC as well as NAMA Index Indicators, with most indicators improving from Band1 to Band 2, approaching Band 3, in comparison to the pre-intervention results in 2021 when the Baseline Evaluation resulted in only 15% (5/32) indicators achieving Band 2. The findings also provided some rich insights into the impact of parent’s participation in their child’s learning and well-being, their child’s school life, and adhering positively to the school requirements. This research